Dental health knowledge, attitude and behavior among first year university students, Mosul. - Saher S Gasgoos; Karam H Jazrawi; May Gh Al-Ajrab (University of Mosul, College of Dentistry, 2007)
Aims: To determine the level of oral health knowledge, attitude and behavior among first year university students in Mosul city, to compare this level among different Colleges also between males and females. Then the obtained results were compared with those of other studies carried out on similar age groups in other countries, to see if there was any significant difference between them. Materials and Methods: Nine Colleges were randomly selected from Mosul University, from each College a fifty random sample was selected to complete the questionnaires in the classroom. The questionnaires' language was in Arabic included a number of questions related to oral health knowledge, attitude and behavior. Incomplete questionnaires were neglected. The size of the sample was 425 students, 216 males and 209 females. Statistical analysis included calculation of frequency, percentage of answers, and chi-square test. Results: Most of the students (93.2%) brushed their teeth and the majority of them (54.8%) engaged in once daily brushing, less than half of them (48.7%) using other means of teeth cleansing aids. A large percent of them had no ideas about the causes of dental caries (75.5%), and how to avoid it (76%). Their knowledge was poor regarding the age at which the primary and permanent teeth erupted( 23.8%, 22.8%) and completed (18.6%, 27.3%). More than half of the students (54.6%) had gingival bleeding but they didn't know the cause of the bleeding (75.1%) and how to avoid it (75.5%). Most of them like eating sweets (82.1%). Small percent (22.4%) knew what is fluoride and its benefit in reducing dental caries (17.9%). Regarding sex differences, females' answers were in general better than those for males. Conclusion: College students seemed to have appropriate knowledge and behavior on some oral health topics but these were limited on the others. Health education needs to be done at universities for enhancing their knowledge attitude and behaviors